Alkalinitetens betydelse för vattenåtgången i en skrubber - En experimentell jämförelse av olika vattentyper - Persson, Anders; Ousbäck, Felix (My University, 2015)
The shipping sector is facing considerable challenges as the demands to reduce emissions from ships are increasing. The International Maritime Organization has, within certain areas, recently lowered the maximum allowed sulfur content in marine fuel, which complicates the use of heavy fuel oil. An alternative to using relatively expensive low-sulfur fuels in ship operations is to install exhaust gas cleaning equipment. Using scrubber technology, the concentration of sulfur oxides in the exhaust gases may be reduced to an acceptable level. Certain types of scrubbers are using sea water in the exhaust cleaning process and it has been shown that the water's alkalinity may be crucial for the desulfurization efficiency, and therefore also the water consumption in the scrubber. The water in the Baltic Sea, which is one of the areas where the new sulfur directive applies, generally has a low and also widely varying alkalinity. Therefore the efficiency of scrubber operation within this area is uncertain. The aim of this study is to experimentally investigate theories about the significance of alkalinity for efficiency and water usage in a scrubber. Water has been collected in six different locations along the coast of Sweden, of which three are in the Baltic Sea. These water samples with varying alkalinity have then been used in a small-scale model scrubber to desulfurize exhaust gases. The results indicate a relatively clear correlation between alkalinity in the process water and scrubber desulfurization efficiency. The theory that a lower alkalinity lowers the resulting degree of purification per volume of water seems to be confirmed. Finally reported, is a series of calculations estimating how much the water consumption in a scrubber may increase in proportion to a decreasing alkalinity of the water used.
Keywords: Annan teknik; Transport; Other Engineering and Technologies; Transport